CD28 and chemokine receptors: Signalling amplifiers at the immunological synapse - Molon, Barbara; Liboni, Cristina; Viola, Antonella (Frontiers in Immunology, 2022)
T cells are master regulators of the immune response tuning, among others, B cells, macrophages and NK cells. To exert their functions requiring high sensibility and specificity, T cells need to integrate different stimuli from the surrounding microenvironment. A finely tuned signalling compartmentalization orchestrated in dynamic platforms is an essential requirement for the proper and efficient response of these cells to distinct triggers. During years, several studies have depicted the pivotal role of the cytoskeleton and lipid microdomains in controlling signalling compartmentalization during T cell activation and functions. Here, we discuss mechanisms responsible for signalling amplification and compartmentalization in T cell activation, focusing on the role of CD28, chemokine receptors and the actin cytoskeleton. We also take into account the detrimental effect of mutations carried by distinct signalling proteins giving rise to syndromes characterized by defects in T cell functionality.